A Short Review of Hydrophilic Surface Modification Methods for Low Density Poly Ethylene - C. K. M., Faizal; Mohib Reza, Kazimi; Iqbal, Ahmed (2011)
In this review, the effect of chemicals, flame radiation, grafting and their combination on the surface of low density polyethylene (LDPE)were studied.Like the most of the polymers, LDPE is inherently hydropolic; we explored the possible options for redenring the polymer surface hydrophilic without changes in bulk properties of the polymer producing improved wettability mainly due to introduction of function group moieties. It was concluded that wettability was associated with concentration and types of functional groups and consequent changes in the contact angle. It was also found that each method for introducing hydrophilicity has advantages and disadvantages of its own and a combination of methods can be applied catering a specific demand. This introduction of wettability would greatly benefit in enhancing innovative use of LDPE in industrial end products like wetting agents, protective films, anti-static fibers, antifogging surfaces, printable polymers and many others related goods.